Edible Bird's Nest as a Potential Cognitive Enhancer - Loh, Su-Peng; Cheng, Shi-Hui; Mohamed, Wael (Frontiers in Neurology, 2022)
Cognitive enhancement is defined as the augmentation or expansion of the mind's fundamental capabilities through the improvement or enhancement of internal or external information processing systems. Various non-pharmacological and pharmacological enhancers had been studied as these are highly sought after to increase cognitive performance. Edible bird nest (EBN) is a natural food substance derived from edible velvet nest saliva. Dietary EBN supplementation has been documented to promote brain development in mammals. The bioactivity and nutritional benefit of EBN are significant during periods of rapid brain development, especially in preterm infants. However, the impact of EBN on learning and memory control remains unknown. This review article aims to illustrate the neuroprotective benefits of EBN and its potential effects as a cognitive enhancer drug.